Hubungan Tingkat Kecemasan Dengan Kejadian Hipertensi Pada Lansia Di Puskesmas Andalas Padang - Azratul Fajar; Fanny Ayudia; Diana Arianti (CV. ITTC INDONESIA, 2026)
The elderly are an age group vulnerable to degenerative diseases, one of which is hypertension, often influenced by psychological factors such as anxiety. In Indonesia, in 2021, the prevalence of hypertension increased to 34.1%. Based on data from the Padang City Health Office in 2023, as many as 51.67% of the elderly suffered from hypertension, along with indications of anxiety among elderly patients with hypertension. Anxiety can trigger an increase in blood pressure through physiological mechanisms, potentially worsening hypertension in the elderly. The purpose of this study was to determine whether there is a significant relationship between anxiety levels and the incidence of hypertension among the elderly at Andalas Public Health Center, Padang. This study employed a quantitative method with a descriptive correlational design using a cross-sectional approach. The research was conducted at Andalas Public Health Center, Padang, from May 6 to May 19, 2025. The population consisted of 285 elderly patients with hypertension aged 60–74 years who visited the health center. A total of 74 respondents were selected using accidental sampling. Data were collected using the Hamilton Anxiety Rating Scale (HARS) questionnaire and blood pressure measurements. Data analysis was carried out using univariate and bivariate methods. The results of the study showed that out of 74 respondents, 11 (14.9%) elderly people experienced severe anxiety. Of the 74 respondents, 33 (44.6%) experienced stage II hypertension. There was a significant relationship between anxiety levels and hypertension incidence in the elderly at the Andalas Padang Community Health Center in 2025. The conclusion of this study is that there is a meaningful relationship between anxiety levels and the incidence of hypertension among the elderly at Andalas Public Health Center, Padang. It is recommended that healthcare providers pay greater attention to psychological aspects, particularly anxiety, in delivering nursing care to elderly patients with hypertension, and intensify education and preventive efforts to reduce the risk of complications.